1980
DOI: 10.1097/00003246-198003000-00018
|View full text |Cite
|
Sign up to set email alerts
|

The effect of newer antiarrhythmic drugs on defibrillation threshold

Abstract: This study was conducted to determine the effects of clofilium phosphate and bretylium tosylate on ventricular defibrillation threshold. Dogs were anesthetized with pentobarbital and subjected to repeated fibrillation-defibrillation episodes. Defibrillation thresholds were determined at 15-min intervals using underdamped 5-6 msec sinusoidal current shocks, from 30 min before drug injection to 120 min after injection. Eight dogs were given clofilium phosphate (0.34 mg/kg, iv). Another 10 dogs were given bretyli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
9
1

Year Published

1986
1986
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(12 citation statements)
references
References 10 publications
2
9
1
Order By: Relevance
“…Our observed effects of D M following lidocaine and bretylium are in accordance with previous studies (6,7) in pentobarbital anesthetized non-CPR dogs. In the previous study (6), a 3 mg/kg intravenous dose of lidocaine was shown to significantly increase DFT, but the onset of such an effect (at 20-30 min) was much delayed in comparison to our study (7).…”
supporting
confidence: 93%
See 2 more Smart Citations
“…Our observed effects of D M following lidocaine and bretylium are in accordance with previous studies (6,7) in pentobarbital anesthetized non-CPR dogs. In the previous study (6), a 3 mg/kg intravenous dose of lidocaine was shown to significantly increase DFT, but the onset of such an effect (at 20-30 min) was much delayed in comparison to our study (7).…”
supporting
confidence: 93%
“…In the previous study (6), a 3 mg/kg intravenous dose of lidocaine was shown to significantly increase DFT, but the onset of such an effect (at 20-30 min) was much delayed in comparison to our study (7). This difference may be attributable to differences in the anesthesia as well as experimental condition.…”
contrasting
confidence: 88%
See 1 more Smart Citation
“…153,[155][156][157][158][159][160] Bretylium also makes defibrillation easier by lowering the electrical defibrillation threshold (DFT) (electrical energy needed to defibrillate the heart) compared with lidocaine and other class 1 drugs, all of which increase the DFT. 248 Indeed, bretylium may be given to any pulseless patient because in patients with cardiac standstill or severe hypotensive bradycardia, bretylium will increase impulse formation and powerfully potentiate administered catecholamines if they are needed to support blood pressure, as shown by Shifrin et al 154 in their septic shock patients. This would decrease the damage to the myocardium caused by excessive catecholamine administration and damage by frequent countershocks, as shown by the studies of Menegazzi et al 249 The ACLS protocol recommendation for immediate electrical countershock as the first step in resuscitation has a number of serious disadvantages.…”
Section: Bretylium Is a Unique Antifibrillatory Drugmentioning
confidence: 99%
“…Such a low dose of quinidine, although unlikely to cause adverse effects, can apparently facilitate electrical cardioversion, presumably by inhibiting vagal tone and prolonging refractoriness. Although results of some experimental studies 31,32 indicate that quinidine increases the energy needed for cardioversion, these findings could not be reproduced in other studies. 33 It is recommended that human patients receive quinidine 24 to 48 hours prior to cardioversion to prevent early relapse of atrial fibrillation.…”
mentioning
confidence: 90%